Random telegraph signal noise in advanced high performance and memory devices - Claeys, C.; De Andrade, M. G.C. [UNESP]; Chai, Z.; Fang, W.; Govoreanu, B.; Kaczer, B.; Zhang, W.; Simoen, E. (Institute of Electrical and Electronics Engineers (IEEE), 2016)
Random Telegraph Signal noise has been extensively studied for more than 30 years and gained high interest in recent years due to its importance for scaled down technologies. This review will demonstrate the power of RTS for single defect characterization. Present understanding of the device physics and evolutions in RTS characterization are highlighted. Special attention is given to RTS in memory devices such as DRAMS, ReRAM, planar (2D) and vertical (3D) flash.
Keywords: interface traps; low frequency noise; oxide traps; random telegraph signal; ReRAMs; time lag plot; UTBB SOI